2010
DOI: 10.1590/s0102-67202010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Imunossupressão com tacrolimus favorece a regeneração hepática induzida por hepatectomia extensa em ratos

Abstract: DESCRITORES -Tacrolimo. Hepatectomia. Regeneração hepática.RESUMO -Racional -A regeneração hepática representa o resultado de respostas fisiológicas que ocorrem após perdas de parênquima, como consequência de agressões tóxico-medicamentosas, infecciosas, traumáticas ou cirúrgicas. Objetivo -Avaliar, em dois momentos distintos da regeneração hepática, a influência do tacrolimus sobre o fenômeno da regeneração hepática desencadeada pela ressecção de 70% do parênquima hepático em ratos plenamente desenvolvidos. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Data from the metaanalysis by Novak et al 8 showed that glutamine supplementation may be associated with a reduction in infectious complications, oxidative stress and mortality rates in critically ill patients. Liver regeneration evaluated by the Kwon formula in the work of Gama Filho et al 9 was significant in the control group as in the experiment one (using Tacrolimus) in the first 24 hours and on the seventh posthepatectomy day. When the values were compared within each group there was an increase in both, more pronounced in the study group.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Data from the metaanalysis by Novak et al 8 showed that glutamine supplementation may be associated with a reduction in infectious complications, oxidative stress and mortality rates in critically ill patients. Liver regeneration evaluated by the Kwon formula in the work of Gama Filho et al 9 was significant in the control group as in the experiment one (using Tacrolimus) in the first 24 hours and on the seventh posthepatectomy day. When the values were compared within each group there was an increase in both, more pronounced in the study group.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 88%
“…Glutamine supplementation to rats leads to increased replication of hepatocytes with 24h, being beneficial to liver regeneration 7 . In their study testing the effect of tacrolimus on liver regeneration, Gama Filho et al 9 found inter-and intragroup statistical difference in periods of 24 hours and seven days, with a gradual increase in the mitotic index, therefore concluding that the more time under the action of Tacrolimus, the greater the positive effect on liver regeneration, which does not corroborate the results of this work, where we found a greater number of intragroup mitosis (glutamine group) only at 72 hours of the experiment (p = 0.003). Among groups there was a trend towards statistical significance (p = 0.056).…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…O Ki67 é um antígeno nuclear expresso nas fases G1, S, G2 e M do ciclo celular. A avaliação imunohistoquímica de Ki67 é utilizada para quantificar a atividade celular proliferativa 45,46 , e atualmente é considerada o padrão ouro para este fim.…”
Section: A Palavra Laser Significa Light Amplification By Stimulated ...unclassified
“…Os espectros de autofluorescência celular abrangem a maior parte da faixa espectral visível ao olho humano, uma vez que, diferentes fluoróforos endógenos emitem diferentes comprimentos de onda, como as flavinas, NAD e lipofuscina emitem luz verde, azul e laranja, respectivamente, quando excitados em comprimentos de onda apropriados 46,47 .…”
Section: Espectroscopia De Fluorescênciaunclassified
See 1 more Smart Citation